Can 1figr Figure into Your Assessment? A Case Study on the Use of 1Figr for A Serials Review. Issue 4 (2nd October 2019) - Hartnett, Eric; Tabacaru, Simona
ABSTRACT: Over the years, libraries have taken numerous approaches to assess their serial subscriptions. When the Texas A&M University Libraries made the strategic decision to introduce a sustainable, iterative approach to reviewing serials they employed a new tool to the task, 1Science's 1Figr product, which includes reports that combine traditionally used usage and citation analysis data together with new open access metrics. This case study examines the reports and how they were employed in the review to help the Libraries' make substantive collection decisions. This article should help libraries get a better understanding of what 1Figr is and how it can be used so that libraries can make an informed decision as to whether the product would be a worthwhile investment for them.